Spór o białorutenizację Kościoła katolickiego na Białorusi - Dworzecka, Joanna (Collectanea Theologica, 2016)
Belorussification is explained as the process of change of direction of the local Roman Catholic Church from Polish national to Belarussian. It aims to becoming an independent Church as the religious standalone institution on the area of the autonomous Republic of Belarus. In practice it primarily means the change of the language used in the local Church. It causes an opposition on the part of the faithful (mainly from the older generation) and the Union of Poles in Belarus. The dispute about belorussification incorporates political, identity, historical and practical issues. The Synod of the Archdiocese of Minsk-Mohilev, Pinsk and Vitebsk in 2000 ordained both languages (Polish and Belarussian) as languages of the Roman Catholic Church in dioceses participating in the synod in Belarus. It depends on priests’ decision in what language they communicate with faithful and celebrate the church liturgical services. Basically the priests want to fulfill their role as pastors and hence they choose the language suitable to communicate with the faithful – Belarussian and even Russian, whereas Polish is used for prayers only where it is explicitly mentioned. The choice made by them is not dictated by political organizations, but it is the conscious and calculated decision considering the neeeds of the faithful, the political correctness and personal attitude towards missionary work. The paper is an attempt to respond to the accusation of Roman Dzwonkowski, Ewa Golachowska and Zdzisław Winnicki who claim that the churches at present have become a tool of belorussification of Poles, in particular children and teenagers, by the clergy which has come from Poland. The subject raised in this thesis aims at explaining the decision of the priests who choose belorussification, by taking into account their perspective and the historical-political context.